Ghrelin Promotes Proliferation and Inhibits Differentiation of 3T3-L1 and Human Primary Preadipocytes - Miao, Hui; Pan, Hui; Wang, Linjie; Yang, Hongbo; Zhu, Huijuan; Gong, Fengying (Frontiers in Physiology, 2019)
Objective: Ghrelin is a 28 amino acid peptide that regulates energy hemostasis, glucose and lipid metabolism. We aimed to explore the effects of ghrelin on proliferation and differentiation of 3T3-L1 and human primary preadipocytes. Methods: 3-(4,5-Dimethylthiazol-2-yl) 2,5-diphenyl tetrazolium bromide (MTT) spectrophotometry, Oil Red O staining, intracellular glycerol-3-phosphate dehydrogenase (G-3-PDH) assays and semiquantitative reverse transcription polymerase chain reaction were used to investigate the action of ghrelin. Results: Ghrelin (0.01-1000 ng/ml) signiﬁcantly increased the numbers of 3T3-L1 cells and the maximum stimulatory effect was observed at 10ng/ml ghrelin treatment for 24h (p<0.05). Ghrelin also promoted the proliferation of human primary preadipocytes from 24h (p<0.05) to 48h (p<0.05) at the concentration of 1000 ng/ml. Further investigation showed that IGF-1 levels were notably increased in ghrelin-treated 3T3-L1 and human preadipocytes, and IGF-1 antibody was capable to attenuate this stimulatory action of ghrelin (all p<0.05). Additionally, ghrelin signiﬁcantly suppressed the differentiation of 3T3-L1 and human primary preadipocytes. 10ng/ml ghrelin notably downregulated G-3-PDH activities in 3T3-L1 cells at day 3 and in human cells from day 4 to 12 following differentiation (all p<0.05), and the intracellular lipoprotein lipase (LPL) mRNA levels were reduced compared with the controls (p<0.05). Further investigation showed that the mRNA levels of peroxisome proliferator-activated receptor γ2 (PPARγ2) and CCAAT/enhancer binding proteinα (C/EBPs) were also suppressed in ghrelin-treated human differentiating adipocytes. Conclusion: Ghrelin promotes the proliferation of 3T3-L1 and human primary preadipocytes by increasing the expression of IGF-1. Ghrelin inhibits murine and human adipocyte differentiation via downregulating PPARγ2 and C/EBPα levels, consequently leading to the decreased lipid accumulation and lipogenic enzymes expression.